2020
DOI: 10.7759/cureus.10898
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Induced Focal Segmental Glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is a common cause of nephrotic syndrome affecting adults and children. Collapsing focal segmental glomerulosclerosis (FSGS), one of five histologic variants of FSGS is described as segmental or global collapse and sclerosis of the glomerular tufts and has been frequently associated with human immunodeficiency virus-associated nephropathy (HIVAN). Its association with other viral and non-viral causes, medications and other disease states has since been established. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…CG was reported in 19 out of 30 native kidney biopsy studies which encompassed a total of 40 patients[ 13 - 30 ]. The median age of this cohort was 55 years with a predominance of males (80%) and black ethnicity (92.5%).…”
Section: Resultsmentioning
confidence: 99%
“…CG was reported in 19 out of 30 native kidney biopsy studies which encompassed a total of 40 patients[ 13 - 30 ]. The median age of this cohort was 55 years with a predominance of males (80%) and black ethnicity (92.5%).…”
Section: Resultsmentioning
confidence: 99%
“…FSGS accounts for 40% of nephrotic syndromes in adults and 20% of nephrotic syndromes in children, and is considered the most common primary glomerular disease resulting in end-stage renal disease in the United States [ 1 ]. The collapsing variant is one of five histological variants of FSGS and appears to be more often linked with viral causes than the other subtypes, specifically HIV [ 4 ]. Although the association of collapsing FSGS with HIV and CMV is relatively established, the COVID-19 pandemic has provided new cases of collapsing FSGS in patients without either of the aforementioned viruses and only infection with the novel SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Shetty et al (2021) analyzed the relationship between COVID-19-associated glomerular disease, in which they found that the glomerular disease caused by COVID-19 was either FSGS, podocytopathy, or both [ 6 ]. Multiple case reports including a report by Malik et al (2020) also suggest a causal relationship between COVID-19 infection and FSGS [ 4 ]. Considering all the previous studies, and a negative viral panel in our patient, including HIV, Hepatitis B and C, and CMV, suspicion was strengthened for her glomerulopathy being a result of her COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%